2023
DOI: 10.1111/zph.13081
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐environmental factors associated with the occurrence of triatomines (Hemiptera: Reduviidae) in an endemic municipality in northern Minas Gerais, Brazil

Thainara da Silva Gonçalves,
Renata Luiz Ursine,
Miriam Cardozo
et al.

Abstract: Triatomines are the vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. The study aimed to evaluate the association between sociodemographic and environmental factors, and changes in land use and cover, with the occurrence and abundance of triatomines by census sectors in an endemic municipality of northern Minas Gerais, Brazil. The study was conducted in Montes Claros, located in the north of Minas Gerais, Brazil. The entomological data used in the study were collected by active surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Our results showed a positive association between surrounding green vegetation and domestic infestation risk, in agreement with some studies in different settings [ 17 , 18 ]. High vegetation cover may be linked to a greater availability of refuges and hosts for sylvatic triatomine species, depending on the epidemiological scenario [ 18 21 ]. In the context of vector control interventions, house spraying with insecticides may trigger triatomine dispersal from the infested house to sylvatic or extra-peridomestic habitats and maintain a latent risk of house (re)infestation from these sources [ 57 ], especially where T. infestans has numerous sylvatic foci as in Bolivia [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed a positive association between surrounding green vegetation and domestic infestation risk, in agreement with some studies in different settings [ 17 , 18 ]. High vegetation cover may be linked to a greater availability of refuges and hosts for sylvatic triatomine species, depending on the epidemiological scenario [ 18 21 ]. In the context of vector control interventions, house spraying with insecticides may trigger triatomine dispersal from the infested house to sylvatic or extra-peridomestic habitats and maintain a latent risk of house (re)infestation from these sources [ 57 ], especially where T. infestans has numerous sylvatic foci as in Bolivia [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Brito et al [ 20 ] found a negative association between house infestation with Rhodnius neglectus and NDVI values adjusted for municipality-level socioeconomic indices in Tocantins, Brazil. Gonçalves et al [ 21 ] revealed that NDVI values adjusted for sociodemographic characteristics at the census tract level were positively related to the occurrence of triatomines in northern Minas Gerais, Brazil. However, the environmental scenarios and the ecological features of the main triatomine vector in the Argentine Chaco, mainly its degree of domiciliation and the virtual absence of sylvatic foci, are different from those addressed in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%